Food waste awareness among Italian university students: results of an online survey - Catalano, Federica; Cassano, Velia; Pujia, Arturo; Sciacqua, Angela; Hribal, Marta Letizia (Frontiers in Nutrition, 2024)
Introduction: Food waste (FW) represents a significant social and environmental problem, with 1.3 billion tons of food wasted yearly worldwide. Even if consumers are increasingly aware of the phenomenon, it remains relevant, and understanding the behaviors of specific target audience segments appears instrumental to the planning of effective interventions. To this end, we designed an observational study to investigate, throughout an online questionnaire, FW-related habits of university students in a Southern Italian region. Methods: A representative sample of 431 students from the University of Catanzaro Magna Graecia completed an online survey aimed at investigate FWrelated behaviors. A descriptive analysis was performed on the whole cohort, and a formal statistical analysis was carried out after excluding responders who had not correctly followed the survey instructions (n=85). Differences were assessed by chi square (χ2) tests. A food wasting score was generated, and differences in the score values were analyzed by Student T-test.Linear and multiple regression analyses were performed to identify factors contributing to the score. Results: Overall, the results of our survey show a high prevalence of virtuous behaviors in the food purchasing phase; while, at home, less than 50% of respondents apply easy-to-implement waste prevention rules. The statistical analysis showed that the major determinants of FW were: no direct involvement in grocery shopping and male gender. Indeed, even if we observed several significant differences comparing subgroups based on established or putative determinants of FW behaviors, none survived matching for group size, gender and relevant food managing (shopping, storing, cooking) habits. The only exception was the more appropriate handling of "use by" products by respondents who received structured nutrition teaching, as opposed to students whose academic courses do not include this subject (adjusted p=0.008). Conclusion: Our data suggest that young adults are trying to implement strategies to reduce FW, even if there is room for improvement, particularly in the storage phase. Extending nutrition education to all university programs may be helpful in reaching this goal.